1997
DOI: 10.3109/03009749709115825
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Histological and Ultrastructural Inflammatory Changes in Spondyloarthropathy and Rheumatoid Arthritis

Abstract: To determine the prevalence of morphologic bowel lesions in patients with inflammatory rheumatic diseases and to better define the interactions between intestinal and articular pathology, 177 patients [39 with reactive arthritis (ReA), 40 with psoriatic arthritis (PsA), 23 with ankylosing spondylitis (AS), 21 with undifferentiated spondyloarthropathy (USpA) and 54 with rheumatoid arthritis (RA)] underwent ileocolonoscopy followed by multiple biopsies of the large bowel and the ileum and ileocecal valve. Biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 7 publications
2
19
1
1
Order By: Relevance
“…These findings have been confirmed (Table 1), but with important differences that relate to the lower prevalence of the abnormalities in ReA and AS, the location of the inflammation, and, in the study by Porzio et al (19), a much lower prevalence of ileitis in B27-negative AS. Three studies (19)(20)(21) demonstrated that intestinal inflammation was equally or more prevalent in the colon than the ileum in patients with ReA or AS, whereas in the studies from Belgium the colon was found to be normal.…”
Section: Spa and Intestinal Diseasesupporting
confidence: 71%
See 2 more Smart Citations
“…These findings have been confirmed (Table 1), but with important differences that relate to the lower prevalence of the abnormalities in ReA and AS, the location of the inflammation, and, in the study by Porzio et al (19), a much lower prevalence of ileitis in B27-negative AS. Three studies (19)(20)(21) demonstrated that intestinal inflammation was equally or more prevalent in the colon than the ileum in patients with ReA or AS, whereas in the studies from Belgium the colon was found to be normal.…”
Section: Spa and Intestinal Diseasesupporting
confidence: 71%
“…Leirisalo-Repo et al (20) reported the presence of histologic lesions in the colon or ileum in 50% of patients with rheumatoid arthritis (RA) and 28% of "controls." Some of these differences are almost certainly due to subjective interpretation of subtle histologic abnormalities (22); however, the demonstration of a high prevalence of colonic inflammation in SpA and ileocolonic abnormality in RA (19,20,23) cannot be explained on these grounds and requires alternate explanation.…”
Section: Spa and Intestinal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Also, histologic changes were characterized by partial or complete loss of superficial epithelium, lymphocytes, plasma cells, granulocytes, and the presence of vasculitic lesions. [8][9][10][11][12] In these reports, no eosinophilic cells were seen in the histologic examination; however, in our case, we detected distinct eosinophilic infiltration on the bowel wall.…”
Section: Discussioncontrasting
confidence: 47%
“…[17], обследовавших 177 больных РЗ. Для изучения характера и тяжести поражения они проводили множест-венные биопсии слизистой оболочки (из каждого отдела толстой кишки) с последующим гистологическим и ульт-раструктурным анализом.…”
Section: таблицаunclassified